A Meta-Analysis Examining the Impact of Consuming Nitrogen-Free Analogs of Essential Amino Acids on the Progression of Chronic Renal Disease - Mohamed S. Imam; Lama Saud Turki Alrasheedi; Saleh Ali Hassan Alyami; Mahdi Mohammed Ahmed Aljamaan; Khaled Sami Khaled Alnaim; Hussam Mohsen Ayesh Alenzi; Nouf Nawaf Alnufeai; Daad Adnan Saad Almalki; Abdullah S. Alanazi; Saud Saad Frais Alotaibi; Naif Fahad Mashaan Alshaibani; Mohamed E. A. Abdelrahim; et al. (Medicina)
Background and Objectives: We conducted a meta-analysis to assess the impact of nitrogen-free substitutes for essential amino acids on the progression of chronic kidney disease (CKD). Materials and Methods: A comprehensive literature review conducted up to November 2024 identified 15 studies that involved 1596 participants with CKD at baseline; among them, 797 were on very-low-protein diets (LPDs) enriched with nitrogen-free analogs (NFA), while 799 followed a standard LPD. Results: A very-LPD utilizing NFA showed significantly improved estimated glomerular filtration rate (MD, 1.00; 95% CI, 0.35–1.64, p = 0.002), reduced serum creatinine (MD, −0.44; 95% CI, −0.75 to −0.13, p = 0.006), decreased blood urea nitrogen (MD, −35.34; 95% CI, −64.27 to −6.42, p = 0.02), and lower parathyroid hormone levels (MD, −1.25; 95% CI, −2.33 to 0.18, p = 0.02) when compared to a standard LPD in patients with CKD. Nevertheless, the very-LPD with NFA resulted in no significant differences in serum albumin (MD, 0.08; 95% CI, −0.03 to 0.19, p = 0.14), serum cholesterol (MD, −17.25; 95% CI, −42.79 to 8.29, p = 0.19), serum phosphorus (MD, −0.41; 95% CI, −0.97 to 0.15, p = 0.15), and serum calcium (MD, 0.16; 95% CI, −0.06 to 0.39, p = 0.16) compared to a typical LPD in subjects with CKD. Conclusions: A very-LPD supplemented with NFA showed a notably higher estimated glomerular filtration rate, decreased serum creatinine levels, lower blood urea nitrogen, and reduced parathyroid hormone levels; however, there were no significant differences observed in serum albumin, serum cholesterol, serum phosphorous, and serum calcium when compared to a standard LPD in individuals with CKD. Additional research is necessary to confirm these results.